Integrated Metabolomics and Transcriptome Analysis of Flavonoid Biosynthesis in Safflower (Carthamus tinctorius L.) With Different Colors - Wang, Rui; Ren, Chaoxiang; Dong, Shuai; Chen, Chao; Xian, Bin; Wu, Qinghua; Wang, Jie; Pei, Jin; Chen, Jiang (Frontiers in Plant Science, 2021)
Safflower is widely used in dying and in traditional medicine, and C-glucosylquinochalcones are the main metabolic species in the red color of safflower. Various safflower cultivars have flowers with different colors. However, the metabolic and transcriptional differences among safflower cultivars with different-colored flowers and the genes participating in C-glucosylquinochalcone biosynthesis are largely unknown. To provide insights on this issue, we performed integrated metabolomics and transcriptome analyses on the flavonoid biosynthesis of flowers of different colors in safflower. The metabolic analysis showed that flavonoid metabolites showed great differences among the different colors of safflower. More flavonoid metabolic species were detected in Y and W, while C-glucosylquinochalcones were not detected in W. The content of C-glucosylquinochalcones increased with increasing color. Transcriptional analysis showed that most of the annotated flavonoid biosynthesis genes were significantly increased in W. The expression of genes related to flavonoid biosynthesis decreased with increasing color. We analyzed the candidate genes associated with C-glucosylquinochalcones, and an integration of the metabolic and transcriptional analyses indicated that the differential expression of the CHS gene is one of the main reasons for the difference in flavonoid species and content among the different colors of safflower. Combined with the expression pattern analysis, these results indicated that HH_035319, HH_032689 and HH_018025 are likely involved in C-glucosylquinochalcones biosynthesis. In addition, we found that their expression showed greatly increased after the MeJA treatment. Therefore, HH_035319, HH_032689 and HH_018025 might participate in C-glucosylquinochalcone biosynthesis, which ultimately leads to the red color in safflower.